Kinetics of C-14 Translocation in Soybean: II. Kinetics in the Leaf - Fisher, Donald B. (1970)
The kinetics of (14)C-assimilates in the soybean leaf were studied in pulse labeling and steady state labeling experiments. (14)C-Sucrose apparently served as the ultimate source, at least, of translocated (14)C-sucrose. However, since the specific activity of leaf sucrose reached a maximum within 5 minutes after pulse labeling, whereas that of exported sucrose did not reach a maximum until at least 20 minutes, it appeared that there were two sucrose compartments in the leaf. A possible physical basis for the two compartments may be the mesophyll (a photosynthetic compartment) and a specialized “paraveinal mesophyll” (a nonphotosynthetic compartment), through which photosynthate must pass on its way to the veins. The (14)C kinetics of sterol glucoside, and probably esterified sterol glucoside, were similar to those for (14)C-sucrose export. Sterol glucoside was labeled only in its glucose moiety and was the only stem lipid which became strongly labeled during (14)C-sucrose translocation. These sterol derivatives may act as membrane carriers of sucrose between the translocation stream and surrounding cells. The kinetics of (14)C-sucrose and its movement to the veins are discussed with reference to compartmentation within the leaf and metabolic exchange with other compounds, particularly with starch. Although a simple compartmental model gave a fairly accurate description of (14)C-sucrose kinetics, an entirely accurate model could not be provided, primarily because of loss of (14)C from sucrose, at an unknown rate, to starch.